THE ROLE OF GREEN MANAGEMENT IN ACHIEVING ORGANIZATIONAL SUSTAINABILITY A CASE STUDY IN KUFA CEMENT PLANT / NAJAF GOVERNORATE - Mohanad Abdul abbas Jasim AL-Janabi (Scholar Express Journals, 2023)
Green management(GM) is a new management concept discussed and presented in this paper. (GM)can be distinguished from both environmental management(EM) and pro- (EM) , is based on idea of sustainable development(GM) is a field that helps to integrate environmental goals , strategies into overall strategic development goals of organization to reach an effective (EM) system to achieve various advantages that benefit , distinguish organization. There are far-reaching repercussions of human industrial activities that have led to the extinction and endangerment of many life forms. Upon realizing this alarmingly growing threat to its survival, industrial human activities began to transform themselves which led to discussions about newer concepts such as It. Hence, this paper attempts to provide a basic overview of the concept of (GM) at the introductory level and discuss different types of (GM) strategies adopted by organizations. The paper attempts to contribute to the emerging field of (GM) and the organizational sustainability(OS) of stakeholders. IT research aims to demonstrate role of green management in achieving (OS) for a sample of the workforce at the Kufa cement plant in Najaf Governorate amounted to (82) working personnel , a number of statistical means were used to prove the validity of the research hypotheses The paper attempts to contribute to the emerging field of (GM) and organizational sustainability(OS) of stakeholders. The current research aims to demonstrate the role of green management in achieving organizational sustainability for a sample of workforce at the Kufa cement plant in Najaf Governorate amounted to (82) working personnel , a number of statistical means were used to prove the validity of the research hypotheses The paper attempts to contribute to the emerging field of (GM) , the (OS) of stakeholders. The current research aims to demonstrate the role of (GM) in achieving (OS) for a sample of the workforce at the Kufa cement plant in Najaf Governorate amounted to (82) working personnel and a number of statistical means were used to prove the validity of research hypotheses
Keywords: Green management; Organizational sustainability